Sistem Informasi Aduan Masyarakat Banyumas Berbasis Android - Engelberta Ceria Kristina; Endang Setyawati; Lyna wati (LPPM Poltek ST Paul, 2023)
One of the efforts to make the community participate in the government's efforts to improve public services is public complaints. When making complaints manually, for example in the suggestion box, many who are pessimistic are not conveyed. Based on the background above, the researcher formulated the problem of this study, namely how to build an Android-based Banyumas Community Complaint Information System to produce an interactive system for public complaint services? So that the public can complain regarding issues that are often complained about regarding health, education, tourism, roads, and disasters to the relevant agencies, besides that the community can check whether their complaints have been submitted or not. Stakeholders involved are the community, super admin, service admin and leadership. This Android-based Banyumas Community Complaint Information System exists to make it easier for the public to submit their complaints directly to the Banyumas Regency government. The benefits of the Android-Based Banyumas Community Complaint Information System enable the community to actively submit complaints about the implementation of development and management of regional services in the Banyumas Regency environment. This research system development method uses the prototype method. Based on the results of the benefit test, the average value of Usability is 94.1%, Integrity is 89.75%, Correctness is 89.7%, Reliability is 88.25%, and Efficiency is 85.3%. So, it can be concluded that this system can speed up the process in terms of the time it takes to receive complaints.